Local paclitaxel delivery after coronary stenting in an experimental animal model - Dommke, Christoph; Haase, Karl K.; Süselbeck, Tim; Streitner, Ines; Haghi, Dariush; Metz, Jürgen; Borggrefe, Martin; Herdeg, Christian (Thrombosis and Haemostasis, 2007)
The goal of this study was to test the safety and efficacy of local paclitaxel delivery via a newly designed application catheter in an experimental animal study. Drug-eluting stents reduce restenosis in comparison to bare-metal stents. The drug-eluting polymer, however, may exert potential thrombogenic and inflammatory effects. A catheter-based local paclitaxel delivery offers further advantages, particularly a homogenous drug transfer into the vessel wall and a pharmacotherapy of the stent edges. In 30 pigs, both bare-metal stent (3.0 × 13mm) implantation and balloon angioplasty were performed. Ten pigs received subsequent local delivery of paclitaxel-solution via a newly designed catheter (Genie™, ACROSTAK corp., Switzerland), 10 animals served as a sham group and received vehicle (0.9% NaCl solution) and 10 animals were used as a control group. All animals were treated with aspirin and clopidogrel to prevent stent thrombosis. After final angiography the vessels were excised 42 days after intervention and prepared for histological and histomorphometric analysis. All coronary arteries showed complete endothelialization 42 days following treatment. Paclitaxel treatment led to a marked reduction of neointimal proliferation either post stent implantation (neointimal area: 1.04 ± 0.10 mm2 vs. 2.37 ± 0.23 mm2, p<0.001) or post balloon dilatation (neontimal area: 0.35 ± 0.14 mm2, vs. 0.68 ± 0.24 mm2, p<0.01).There were no significant angiographic or histomorphometric differences between the control and the sham group. In both paclitaxel groups neither angiographic edge phenomena nor a significant histomorphometric inflammatory response were found in the treated vessel segments. In conclusion, the local application of paclitaxel via the Genie™ catheter is safe and effective to significantly reduce the proliferative response post-stent implantation or balloon dilatation in an experimental animal model.
Keywords: Restenosis; angioplasty; paclitaxel; local drug delivery; Genie™